Growth and Characterization of Co-Doped Fluorine and Antimony in Tin Oxide Thin Films Obtained by Ultrasonic Spray Pyrolysis - Thitinai GAEWDANG; Ngamnit WONGCHAROEN (My University, 2007)
Fluorine (F)-doped, antimony (Sb)-doped, fluorine and antimony co-doped tin oxide (SnO2) thin films were prepared by ultrasonic spray pyrolysis technique using SnCl2, NH4F and SbCl3 as precursors of Sn, F and Sb elements respectively. F and Sb doping concentrations carried out from 1 to 20 wt% and 1 to 4 wt% in F-doped and Sb-doped SnO2 films respectively. In F and Sb co-doped SnO2 films, the proportions of F and Sb to Sn in starting solution were 15 and 2 wt% respectively. XRD patterns showed that the preferred orientation of SnO2:F, SnO2:Sb and SnO2:F, Sb is dependent on the doping concentration. The variation of doping concentration and preferred orientation of the films was reflected in their morphology as investigated by SEM. The electrical properties of the films were performed by Hall effect measurements in van der Pauw configuration. The minimum resistivity values of SnO2:F and SnO2:Sb were found in the films doped with 15 wt% of F and 2 wt% of Sb. However, The minimum of resistivity value of F and Sb co-doped SnO2 films is not better than neither the one of F-doped nor the one of Sb-doped SnO2 films. The optical transmission of SnO2:F films was found to increase with increasing in F doping concentration. Whereas the optical transmission of SnO2:Sb was found to decrease with increasing in Sb concentration. The F and Sb co-doped SnO2 films annealed in three different conditions at 500°C show the lower transmission values than the value obtained in the as-prepared SnO2:F, Sb films.
Keywords: Tin oxide; Gas Sensing Nanomaterials and Sensors